Systematic Characterisation of the Fragmentation of Flavonoids Using High-Resolution Accurate Mass Electrospray Tandem Mass Spectrometry - Candy Jiang; Paul J. Gates (Molecules)
Flavonoids are a class of polyphenolic secondary metabolites found in plants. Due to their ubiquity in our daily dietary intake and their major anti-oxidative, anti-inflammatory and anti-mutagenic activities, they have been a major focus of wide-ranging research for the past two decades. Mass spectrometry combined with liquid chromatography is one of the most popular techniques for the analysis of flavonoids. In this study, high-resolution accurate mass electrospray tandem mass spectrometry was used to study 30 flavonoids in both positive and negative ionisation modes. From the data obtained, common losses were summarised and compiled. Dominating neutral losses were tabulated. The radical loss of CH3· was observed in flavonoids containing methoxy groups and three key diagnostic product ions were identified. These were m/z 153 (indicative of two OH groups on ring A) m/z 167 (indicative of one OH and one methoxy group on ring A) and m/z 151 (a flavanol, with no ketone oxygen but two OH groups on ring A). These will be useful in structural elucidation of unknown flavonoids and flavonoid metabolites. Energy breakdown graphs were utilised to distinguish between three pairs of structural isomers, and to help rationalise proposed fragmentation pathways. Lastly, a competition of loss of CH3· and methane was reported for rhamnetin and isorhamnetin in the negative ion mode for the first time. Proposed fragmentation pathways were given to rationalise the differences in peak intensities for this competitive process.